Staying Alive: Long-Term Success of Bottlenose Dolphin Interventions in Southwest Florida - McHugh, Katherine A.; Barleycorn, Aaron A.; Allen, Jason B.; Bassos-Hull, Kim; Lovewell, Gretchen; Boyd, Denise; Panike, Anna; Cush, Carolyn; Fauquier, Deborah; Mase, Blair; Lacy, Robert C.; Greenfield, Michelle R.; et al. (Frontiers in Marine Science, 2021)
Small cetaceans face persistent threats from fisheries interactions, making effective mitigation a priority for conservation. In southwest Florida, interactions come primarily from small-scale recreational hook and line and trap/pot fisheries, with regional stranding network partners working with federal agency managers to assess and intervene as possible in cases of live animal entanglement. Evaluating success of intervention cases is difficult due to financial and logistical constraints which may preclude detailed follow-up monitoring. Survival over the initial six weeks post-release has been used as a marker of short-term success for small-cetacean rescue and/or rehabilitation cases. Early intervention prior to stranding, especially via remote disentanglement or rescue and immediate re-release onsite, can save entangled free-ranging dolphins facing life-threatening anthropogenic injuries. However, given the costs associated with interventions, it is important to understand the benefits of these endeavors not only to save individuals, but also to establish if and how saved individuals contribute to social functioning, survival and reproduction within small, resident populations facing multiple concurrent threats. Here we provide evidence from 27 well-documented bottlenose dolphin (Tursiops truncatus) intervention cases during 1985-2019 where follow-up monitoring over multiple years sheds light on the longer-term success of these efforts and potential benefits to local populations. Nearly all rescued individuals (92%) survived longer than six weeks post-release (mean minimum survival period = 5 yrs, range 0-35 yrs), with 13 still observed frequently within their prior resident communities, in good physical health, and engaging in normal behavior. Survivorship rates did not decline substantially between one and five years post-rescue, meaning survival beyond one year may be a useful benchmark of long-term success. Rescued females that reached reproductive maturity (n=4) have produced 12 post-intervention offspring to date. Social network analysis and demographic modeling applied to cases from the long-term resident community in Sarasota Bay confirmed that animals maintain social connections post-intervention and that interventions result in higher population growth rates. While not every intervention succeeds, this study demonstrates the conservation value of pre-stranding interventions which allow individuals that otherwise would be lost to remain viable and productive members of local populations when prevention of anthropogenic injury is not possible.